PENGARUH CITRA MEREK DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN MOBIL TOYOTA AVANZA DI PT. AGUNG TOYOTA SUTOMO PEKANBARU - Lison, Muhammad Fakhri; Fadli, Mashur (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
The purpose of this study is to determine the effect of Brand Image and Service Quality on Purchase Decision of Toyota Avanza at PT. Agung Toyota Sutomo. This study is a quantitative study with a sample of 73 respondents. The data sources were obtained from secondary data and primary data. This study used a questionnaire as a data collection technique using a purposive sampling method, namely a technique for determining samples with certain considerations or characteristics. The analysis methods used in this study are validity testing, reliability testing, classical heteroscedasticity assumption testing, multiple linear analysis, t-test, F-test and coefficient of determination analysis (R2). The results of this study are Brand Image (X1) has a positive and significant effect on Purchase Decision (Y), Service Quality (X2) doesnt have a positive and significant effect on Purchase Decision (Y), and Brand Image and Service Quality have a positive and significant effect on Purchase Decision. Keywords: Brand Image, Service Quality, Purchase Decision Keywords: Brand Image, Service Quality, Purchase Decision